Study on the role of filament temperature on growth of indium-catalyzed silicon nanowires by the hot-wire chemical vapor deposition technique - Chong, S.K.; Goh, B.T.; Dee, C.F.; Rahman, S.A. (2012)
Silicon nanowires (SiNWs) were synthesized from indium catalysts on the Si(111) substrate using the hot-wire chemical vapor deposition technique. A tungsten filament with purity of 99.95 was employed for both the evaporation of an indium wire as catalyst and the decomposition of the precursor gas silane diluted in hydrogen. In this study, we investigated the role of the filament temperature (T-f) on the growth and structural properties of the SiNWs. A threshold T-f for the successive growth of the SiNWs via a vapor-liquid-solid process was observed at T-f between 1400 and 1500 degrees C. For T-f of 1400 degrees C and below, only a layer of Si shell cladding was formed on the indium core. An increase in T-f above the threshold resulted in a significant increase in the number density and the aspect ratio of the SiNWs. X-ray diffraction and micro-Raman measurements indicated an enhancement in crystallinity of the SiNWs with the increase in T-f. Fourier transform infrared analysis showed an enhancement in the presence of Si-O and Si-H related bonds with the increase in T-f. The Si-O bond is mostly originated from the native oxide layer of SiNWs, while Si-H bond suggests that Si-H-x species were responsible for the growth. (C) 2012 Elsevier B.V. All rights reserved.